Reactions of Phenolic Antioxidants with Electrogenerated Superoxide Anion Radical and Their Analytical Application - Ziyatdinova G.K.; Zakharova S.P.; Budnikov H.C. (Учёные записки Казанского университета: Серия Естественные науки)
Parameters of oxygen electroreduction on glassy carbon electrode modified with multi-walled carbon nanotubes were found. Increase in the oxygen reduction currents and system reversibility was observed compared to unmodified electrode, which allows to use cyclic voltammetry for investigation of reactions of electrogenerated superoxide anion radical with antioxidants. It was revealed that phenolic antioxidants act as proton donors (i.e., as Brønsted acids) and their interaction with superoxide anion radical follows ECE mechanism. The rate constants for reactions of 19 phenolic antioxidants with superoxide anion radical were calculated. The values of these constants were relatively similar, varied in the range of 6.8·104 ÷ 11.0·104 L/mol·s, and thereby reflected the slight influence of the structure of phenolic antioxidants, in particular the number and position of hydroxyl groups, as well as the steric effects of substituents. A volt-ammetric method was developed for evaluation of the superoxide scavenging capacity based on the relative increase in oxygen reduction current in the presence of antioxidants. The approach was tested on 11 samples of medicinal herb tinctures. The superoxide scavenging capacity was expressed in gallic acid equiva-lents per 1 mL of tincture. Positive correlation of the superoxide scavenging capacity with antioxidant activity (r = 0.7083 at rcrit = 0.602) was obtained.